Flame-retardant thermoplastic resin and preparation method thereof
By using PGMA-magnesium ferrate core shells as synergistic flame retardant in thermoplastic resin composites and combining with traditional flame retardant, the problem of insufficient flame retardant performance of existing thermoplastic resins is solved, and the efficient flame retardant performance of thermoplastic resin composites is improved, and its application fields are expanded.
Patent Information
- Application Number
- CN202311405570.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The flame retardant properties of existing thermoplastic resins are insufficient, especially in specific application areas where V-0 level requirements are high, which limits the application range of their composite materials.
The PGMA-magnesium ferrate core shell with PGMA as the shell and magnesium ferrate as the core is used as the synergistic flame retardant, and combined with decabromodiphenylethane or decabromobenzene S ether as the flame retardant, the flame retardant performance of the thermoplastic resin composite material is improved through specific preparation methods and composition ratios.
It significantly improves the flame retardant performance of thermoplastic resin composites, allowing them to meet the V-0 level flame retardant standards, and expands its application range in specific application fields.
Smart Images

Figure SMS_1 
Figure FDA0004516465800000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a flame retardant thermoplastic resin and a preparation method thereof. Background Art
[0002] Thermoplastic resin is a widely used polymer polyester resin. Thermoplastic resin has the advantages of good fatigue resistance, good heat resistance, excellent dimensional stability, etc. However, in some specific home appliance materials (such as air-conditioning motor materials, washing machine motor housing), the flame retardant properties of thermoplastic resin are very high and are required to reach the V-0 level, which limits the application of thermoplastic resin composites in some specific fields.
[0003] In view of these deficiencies, the present invention innovatively synthesizes a flame retardant thermoplastic resin composite material, which has excellent flame retardant properties, and has very important practical significance for expanding the application field of thermoplastic resin composite materials. Summary of the invention
[0004] In view of this, the present invention innovatively synthesizes a flame retardant thermoplastic resin and a preparation method thereof, which has good flame retardant properties and solves the technical problem of limited flame retardant properties of thermoplastic resins in the prior art.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A flame retardant thermoplastic resin composite material is composed of the following components in parts by weight:
[0007]
[0008] The synergistic flame retardant is a PGMA-magnesium ferrite core-shell material with PGMA as the shell and magnesium ferrite as the core.
[0009] In a further embodiment, the thermoplastic resin is one of polyethylene (PE), polypropylene (PP), polystyrene (PS), polybutylene terephthalate (PBT), and polyamide 6 (PA6).
[0010] The flame retardant is decabromodiphenylethane or decabromobisphenol S ether.
[0011] In a further embodiment, the preparation method of the synergistic flame retardant comprises the following steps:
[0012] (1) adding oxalic acid, magnesium nitrate and ferric nitrate into a solvent, stirring to react, and then cooling, washing and filtering to obtain a precursor MgFe2(C2O4)4;
[0013] (2) calcining the precursor MgFe2(C2O4)4 in a muffle furnace to obtain magnesium ferrite;
[0014] (3) adding magnesium ferrite, an initiator, a crosslinking agent, and glycidyl methacrylate into a solvent and heating the reaction; then washing, filtering, and drying the reactants to obtain a PGMA-magnesium ferrite core-shell material having PGMA as a shell and magnesium ferrite as a core.
[0015] Wherein, the stirring reaction in step (1) refers to stirring the reaction at 60-80° C. for 8-16 hours;
[0016] The calcination in step (2) refers to calcination at 720-800°C for 10-16h.
[0017] In step (3), the heating reaction refers to stirring the reaction at 50-70°C for 6-10 hours; and the drying refers to drying in a vacuum drying oven at 40-60°C for 6-8 hours.
[0018] In a further embodiment, the solvent in step (1) or step (3) is acetone, ether or isopropanol.
[0019] In a further embodiment, in step (1), the mass ratio of oxalic acid, magnesium nitrate and ferric nitrate is (10-12):(10-16):(20-24).
[0020] In a further embodiment, in step (3), the mass ratio of magnesium ferrite, initiator, crosslinking agent, and glycidyl methacrylate is (30-40): (0.2-0.4): (0.1-0.3): (16-20);
[0021] The initiator is potassium persulfate, sodium persulfate or azobisisoheptanenitrile,
[0022] The cross-linking agent is dicumyl peroxide or diisopropylbenzene peroxide.
[0023] In a further embodiment, the antioxidant is one or a mixture of Irganox 264, Irganox 1076 and Irganox 1330 produced by BASF.
[0024] Another object of the present invention is to provide a method for preparing the flame retardant thermoplastic resin composite material, comprising the following steps:
[0025] (1) Weigh 80-104 parts of thermoplastic resin, 20-24 parts of flame retardant, 4-6 parts of synergistic flame retardant, and 0.1-0.5 parts of antioxidant, mix and stir to obtain a mixture;
[0026] (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The preparation formula of magnesium ferrite is as follows:
[0029] Mg 2+ +2Fe 3+ +4C2O4 2- →MgFe2(C2O4)4
[0030] MgFe2(C2O4)4+2O2→MgFe2O4+8CO2
[0031] (2) The PGMA-magnesium ferrite core-shell material prepared in the present application is added to the thermoplastic resin as a synergistic flame retardant. During the extrusion granulation process of the composite material, the magnesium ferrite will decompose, and the iron oxide and magnesium oxide produced can promote the carbonization of the thermoplastic resin, thereby improving the flame retardant properties of the thermoplastic resin.
[0032] (3) The PGMA-magnesium ferrite core-shell material prepared in the present application has a PGMA shell that is highly compatible with the thermoplastic resin, which is beneficial for improving the dispersion of magnesium ferrite in the thermoplastic resin and avoiding agglomeration, thereby improving the flame retardant properties of the thermoplastic resin.
[0033] (4) The synergistic flame retardant prepared in the present application is a modified PGMA-magnesium ferrite core-shell material, which has better dispersibility and flame retardancy than commercially available magnesium ferrite, and can also improve the flame retardancy of thermoplastic resins. DETAILED DESCRIPTION
[0034] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0036] The raw materials used in the following examples are as follows:
[0037] PBT (model 1100-211M), Chang Chun Chemical Co., Ltd., Taiwan, China;
[0038] PP (model Z30S), Sinopec Maoming Petrochemical Co., Ltd.;
[0039] PE (model 5070), Panjin Ethylene Co., Ltd.;
[0040] PA6 (Model IM), Kuibyshev Nitrogen (Shanghai) Engineering Plastics Co., Ltd.;
[0041] PS (model 350), Guoqiao, Taiwan, China;
[0042] Oxalic acid, Qingzhou Xinsheng Chemical Co., Ltd.;
[0043] Ferric nitrate, Shandong Haoshun Chemical Co., Ltd.;
[0044] Magnesium nitrate, Shanxi Guangyuan Xinke Chemical Co., Ltd.;
[0045] Acetone, Jinan Xinchaorui Chemical Co., Ltd.;
[0046] Potassium persulfate, Jinan Jiayang Chemical Co., Ltd.;
[0047] Dicumyl peroxide, Shanghai Yubo Biotechnology Co., Ltd.;
[0048] Glycidyl methacrylate, Jinan Kaichuang Chemical Co., Ltd.;
[0049] Decabromodiphenylethane, decabromobisphenol S ether, Wuhan Xinweiye Chemical Co., Ltd.;
[0050] Magnesium ferrite, Shouguang Hongwei Chemical Co., Ltd.;
[0051] Antioxidant (model Irganox264, Irganox1076, Irganox1330), BASF.
[0052] Preparation Example 1
[0053] (1) Weigh 100 g of oxalic acid, 100 g of magnesium nitrate, 200 g of ferric nitrate, and 1.0 kg of acetone, add them to a reaction vessel, and stir at 60° C. for 8 h to prepare solution A;
[0054] (2) Cooling, washing and filtering solution A to obtain precursor MgFe2(C2O4)4;
[0055] (3) placing the precursor MgFe2(C2O4)4 in a muffle furnace and calcining at 720°C for 10 h to obtain magnesium ferrite;
[0056] (4) Weigh 300 g of magnesium ferrite, 2 g of initiator potassium persulfate, 1 g of crosslinker diisopropylbenzene peroxide, 160 g of glycidyl methacrylate, and 700 g of acetone, add them to a reaction vessel, stir and react at 50° C. for 6 h, wash, filter, and dry in a vacuum oven at 40° C. for 6 h to obtain modified magnesium ferrite with PGMA as the shell and magnesium ferrite as the core (PGMA-magnesium ferrite core-shell compound), which is recorded as synergistic flame retardant M1.
[0057] Example 1
[0058] (1) Weigh 84 parts of PP, 20 parts of decabromodiphenylethane, 4 parts of synergistic flame retardant M1, and 0.1 parts of Irganox 1076, mix and stir to obtain a mixture;
[0059] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material P1.
[0060] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 220r / min.
[0061] Comparative Example 1
[0062] (1) Weigh 84 parts of PP, 20 parts of decabromodiphenylethane, 4 parts of magnesium ferrite prepared in step (3) of Preparation Example 1, and 0.1 parts of Irganox 1076, mix and stir to obtain a mixture;
[0063] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PP composite material D1.
[0064] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 220r / min.
[0065] The PP composite materials prepared in the above Example 1 and Comparative Example 1 were made into strips by injection molding and tested. The test data are as follows:
[0066] Test items Test Standards unit P1 D1 Flame retardant grade UL 94 V-0 V-1
[0067] It can be seen from the above table that the flame retardant properties of Example 1 are better than those of Comparative Example 1.
[0068] Preparation Example 2
[0069] (1) Weigh 120 g of oxalic acid, 160 g of magnesium nitrate, 240 g of ferric nitrate, and 1.6 kg of ether, add them to a reaction vessel, and stir at 80° C. for 16 h to prepare solution A;
[0070] (2) Cooling, washing and filtering solution A to obtain precursor MgFe2(C2O4)4;
[0071] (3) placing the precursor MgFe2(C2O4)4 in a muffle furnace and calcining at 800°C for 16 hours to obtain magnesium ferrite;
[0072] (4) Weigh 400 g of magnesium ferrite, 4 g of initiator sodium persulfate, 3 g of crosslinker diisopropylbenzene peroxide, 200 g of glycidyl methacrylate, and 900 g of ether, add them to a reaction vessel, stir and react at 70° C. for 10 h, wash, filter, and dry in a vacuum oven at 60° C. for 8 h to obtain a PGMA-magnesium ferrite core-shell material with PGMA as the shell and magnesium ferrite as the core, which is the synergistic flame retardant M2.
[0073] Example 2
[0074] (1) Weigh 104 parts of PBT, 24 parts of decabromobisphenol S ether, 6 parts of synergistic flame retardant M2, 0.1 parts of antioxidant Irganox 1076, 0.2 parts of antioxidant Irganox 264, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0075] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material P2.
[0076] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 300r / min.
[0077] Comparative Example 2
[0078] (1) Weigh 104 parts of PBT, 24 parts of decabromodiphenylethane, 6 parts of magnesium ferrite prepared in step (3) of Preparation Example 2, 0.1 parts of antioxidant Irganox 1076, 0.2 parts of antioxidant Irganox 264, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0079] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PBT composite material D2.
[0080] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 300r / min.
[0081] The PBT composite materials prepared in the above Example 2 and Comparative Example 2 were made into test strips by injection molding machine, and the test data are as follows:
[0082] Test items Test Standards unit P2 D2 Flame retardant grade UL 94 V-0 V-1
[0083] It can be seen from the above table that the flame retardant performance of Example 2 is better than that of Comparative Example 2.
[0084] Preparation Example 3
[0085] (1) Weigh 110 g of oxalic acid, 130 g of magnesium nitrate, 220 g of ferric nitrate, and 1.3 kg of isopropanol, add them to a reaction vessel, and stir at 70° C. for 12 h to prepare solution A;
[0086] (2) Cooling, washing and filtering solution A to obtain precursor MgFe2(C2O4)4;
[0087] (3) placing the precursor MgFe2(C2O4)4 in a muffle furnace and calcining at 760°C for 13 h to obtain magnesium ferrite;
[0088] (4) Weigh 350 g of magnesium ferrite, 3 g of initiator azobisisoheptanenitrile, 2 g of crosslinker diisopropyl peroxide, 180 g of glycidyl methacrylate, and 800 g of isopropanol, add them to a reaction vessel, stir and react at 60° C. for 8 h, wash, filter, and dry in a vacuum oven at 50° C. for 7 h to obtain modified magnesium ferrite with PGMA as the shell and magnesium ferrite as the core, which is the synergistic flame retardant M3.
[0089] Example 3
[0090] (1) Weigh 94 parts of PE, 22 parts of decabromodiphenylethane, 5 parts of synergistic flame retardant M3, 0.1 parts of antioxidant Irganox 264, and 0.2 parts of antioxidant Irganox 1076, mix and stir to obtain a mixture;
[0091] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material P3.
[0092] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0093] Comparative Example 3
[0094] (1) Weigh 94 parts of PE, 22 parts of decabromodiphenylethane, 5 parts of magnesium ferrite prepared in step (3) of Preparation Example 3, 0.1 parts of antioxidant Irganox 264, and 0.2 parts of antioxidant Irganox 1076, mix and stir to obtain a mixture;
[0095] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PE composite material D3.
[0096] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.
[0097] The PE composite materials prepared in the above Example 3 and Comparative Example 3 were made into test strips by injection molding machine, and the test data are as follows:
[0098] Test items Test Standards unit P3 D3 Flame retardant grade UL 94 V-0 V-1
[0099] It can be seen from the above table that the flame retardant performance of Example 3 is better than that of Comparative Example 3.
[0100] Preparation Example 4
[0101] (1) Weigh 115 g of oxalic acid, 138 g of magnesium nitrate, 225 g of ferric nitrate, and 1.55 kg of acetone, add them to a reaction vessel, and stir at 75° C. for 11 h to prepare solution A.
[0102] (2) Cool, wash and filter solution A to obtain the precursor MgFe2(C2O4)4.
[0103] (3) The precursor MgFe2(C2O4)4 was placed in a muffle furnace and calcined at 765°C for 15 h to obtain magnesium ferrite.
[0104] (4) Weigh 385 g of magnesium ferrite, 2.5 g of initiator potassium persulfate, 2.5 g of crosslinker diisopropylbenzene peroxide, 195 g of glycidyl methacrylate, and 885 g of acetone, add them to a reaction vessel, stir and react at 55° C. for 9 h, wash, filter, and dry in a vacuum oven at 58° C. for 7 h to obtain modified magnesium ferrite with PGMA as the shell and magnesium ferrite as the core, which is the synergistic flame retardant M4.
[0105] Example 4
[0106] (1) Weigh 95 parts of PA6, 23 parts of decabromodiphenylethane, 5.5 parts of synergistic flame retardant M4, 0.1 parts of antioxidant Irganox 1076, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0107] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material P4.
[0108] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0109] Comparative Example 4
[0110] (1) Weigh 95 parts of PA6, 23 parts of decabromodiphenylethane, 5.5 parts of magnesium ferrite prepared in step (3) of Preparation Example 4, 0.1 parts of antioxidant Irganox 1076, and 0.2 parts of antioxidant Irganox 1330, mix and stir to obtain a mixture;
[0111] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PA6 composite material D4.
[0112] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.
[0113] The PA6 composite materials prepared in the above Example 4 and Comparative Example 4 were made into strips by injection molding and tested. The test data are shown in the following table:
[0114] Test items Test Standards unit P4 D4 Flame retardant grade UL 94 V-0 V-1
[0115] It can be seen from the above table that the flame retardant performance of Example 4 is better than that of Comparative Example 4.
[0116] Preparation Example 5
[0117] (1) Weigh 118 g of oxalic acid, 139 g of magnesium nitrate, 234 g of ferric nitrate, and 1.55 kg of acetone, add them to a reaction vessel, and stir at 78° C. for 15 h to prepare solution A;
[0118] (2) Cooling, washing and filtering solution A to obtain precursor MgFe2(C2O4)4;
[0119] (3) placing the precursor MgFe2(C2O4)4 in a muffle furnace and calcining at 795°C for 14 h to obtain magnesium ferrite;
[0120] (4) Weigh 395 g of magnesium ferrite, 3.6 g of initiator potassium persulfate, 2.9 g of crosslinker diisopropylbenzene peroxide, 178 g of glycidyl methacrylate, and 879 g of acetone, add them to a reaction vessel, stir and react at 55° C. for 9 h, wash, filter, and dry in a vacuum oven at 55° C. for 7 h to obtain modified magnesium ferrite with PGMA as the shell and magnesium ferrite as the core, which is the synergistic flame retardant M5.
[0121] Example 5
[0122] (1) Weigh 103 parts of PS, 23.5 parts of decabromodiphenylethane, 4.5 parts of synergistic flame retardant M5, 0.1 parts of antioxidant Irganox 1076, and 0.1 parts of antioxidant Irganox 264, mix and stir to obtain a mixture;
[0123] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material P5.
[0124] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.
[0125] Comparative Example 5
[0126] (1) Weigh 103 parts of PS, 23.5 parts of decabromodiphenylethane, 4.5 parts of magnesium ferrite prepared in step (3) of Preparation Example 5, 0.1 parts of antioxidant Irganox 1076, and 0.1 parts of antioxidant Irganox 264, mix and stir to obtain a mixture;
[0127] (2) The mixed material obtained in step (1) is extruded from an extruder and granulated to obtain a PS composite material D5.
[0128] The twin-screw extruder includes six temperature zones arranged in sequence, wherein the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 220°C, the temperature of the fourth temperature zone is 220°C, the temperature of the fifth temperature zone is 220°C, the temperature of the sixth temperature zone is 220°C, the head temperature of the twin-screw extruder is 220°C, and the screw speed is 280r / min.
[0129] The PS composite materials prepared in the above Example 5 and Comparative Example 5 were made into strips by injection molding and tested. The test data are shown in the following table:
[0130] Test items Test Standards unit P5 D5 Flame retardant grade UL 94 V-0 V-1
[0131] It can be seen from the above table that the flame retardant performance of Example 5 is better than that of Comparative Example 5.
[0132] This shows that the thermoplastic resin composite material prepared by the method provided by the present invention has excellent flame retardant properties and can expand the application field of the thermoplastic resin composite material.
[0133] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0134] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A flame retardant thermoplastic resin composite material, characterized in that: It is composed of the following components by weight: The synergistic flame retardant is a PGMA-magnesium ferrite core-shell material with PGMA as the shell and magnesium ferrite as the core.
2. The thermoplastic resin composite material according to claim 1, characterized in that: The thermoplastic resin is one of polyethylene, polypropylene, polystyrene, polybutylene terephthalate and polyamide 6.
3. The flame retardant thermoplastic resin composite material according to claim 1, characterized in that: The flame retardant is decabromodiphenylethane or decabromobisphenol S ether.
4. The flame retardant thermoplastic resin composite material according to claim 1, characterized in that: The preparation method of the PGMA-magnesium ferrite core-shell material comprises the following steps: (1) adding oxalic acid, magnesium nitrate and ferric nitrate into a solvent, stirring to react, and then cooling, washing and filtering to obtain a precursor MgFe2(C2O4)4; (2) calcining the precursor MgFe2(C2O4)4 in a muffle furnace to obtain magnesium ferrite; (3) adding magnesium ferrite, an initiator, a crosslinking agent, and glycidyl methacrylate into a solvent and heating the reaction; then washing, filtering, and drying the reactants to obtain a PGMA-magnesium ferrite core-shell material having PGMA as a shell and magnesium ferrite as a core.
5. The flame retardant thermoplastic resin composite material according to claim 4, characterized in that: The stirring reaction in step (1) refers to stirring the reaction at 60-80° C. for 8-16 hours; The calcination in step (2) refers to calcination at 720-800°C for 10-16h. In step (3), the heating reaction refers to stirring the reaction at 50-70°C for 6-10 hours; and the drying refers to drying in a vacuum drying oven at 40-60°C for 6-8 hours.
6. The flame retardant thermoplastic resin composite material according to claim 1, characterized in that: The solvents in step (1) or step (3) are acetone, ether or isopropanol.
7. The flame retardant thermoplastic resin composite material according to claim 1, characterized in that: In step (1), the mass ratio of oxalic acid, magnesium nitrate and ferric nitrate is (10-12):(10-16):(20-24).
8. The flame retardant thermoplastic resin composite material according to claim 1, characterized in that: In step (3), the mass ratio of magnesium ferrite, initiator, crosslinking agent and glycidyl methacrylate is (30-40): (0.2-0.4): (0.1-0.3): (16-20); The initiator is potassium persulfate, sodium persulfate or azobisisoheptanenitrile, The cross-linking agent is dicumyl peroxide or diisopropylbenzene peroxide.
9. The thermoplastic resin composite material according to claim 1, characterized in that: The antioxidant is one of Irganox264, Irganox1076 and Irganox1330 or a mixture of several thereof.
10. The method for preparing a thermoplastic resin composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Weigh 84-104 parts of thermoplastic resin, 20-24 parts of flame retardant, 4-6 parts of synergistic flame retardant, and 0.1-0.5 parts of antioxidant, mix and stir to obtain a mixture; (2) Extruding the mixed material obtained in step (1) from an extruder and granulating it to obtain a thermoplastic resin composite material.
Citation Information
Patent Citations
Syndiotactic polystyrene flame-retardant composite material
CN106751077A
Flame-retardant nylon composite material with ultra-low temperature impact resistance and high fluidity and preparation method and application thereof
CN110016226A
High-heat-resistance flame-retardant nylon 66 composite material
CN112358723A
Molding resin
JP1980075445A
Fire retardant compositions containing metal ferrites for reduced corrosivity
US6620348B1